Membentuk Peserta Didik Menjadi Pribadi Ulul al-bab Prespektif Ma’na-Cum Maghza (Kajian Qs. Ar-Ra’d Ayat 19) - Moh. Solikul Hadi; Abdul Kahfi Amrulloh; Khoerul Anwar (Kuras Institute, 2024)
This research explores the formation of students into Ulul al-bab individuals through the Ma'na-Cum Maghza perspective, focusing on the analysis of verse 19 of Surah Ar-Ra'd. The research uses a Quranic studies approach to understand the concept of Ulul al-bab and explore its practical implications in the context of education. Through the interpretation of verse 19, the research identifies factors that support the process of Ulul al-bab's formation and details the implications of Ma'na Cum Maghza in the context of education. The research methodology involves textual and contextual analysis of the verse and an interdisciplinary approach that integrates Islamic educational principles. The results of this study can provide practical guidance for educators in shaping students towards Ulul al-bab individuals through the teachings of the Qur'an and the values of Islamic education. This research has the potential to contribute to a deeper understanding of the development of character and spirituality of students in the context of Islamic education